2019
DOI: 10.1167/iovs.18-25335
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Conjunctival Fibrosis Response Using a 3D Glaucoma Tenon's Capsule + Conjunctival Model

Abstract: PURPOSE. Surgical techniques such as trabeculectomy aim to treat glaucoma by making an incision into the scleral tissue, to create an alternative drainage pathway for aqueous to flow into the sub-Tenon's/subconjunctival space. However, tissue fibrosis and wound healing occurring after the procedures can reduce the success rate. This study aims to investigate the synergistic effects of aqueous humor in combination with shear stress on the fibrosis response occurring in Tenon's capsule and conjunctival tissue (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Intraoperative drug delivery is one of the key ways of preventing and treating ocular fibrosis, yet in vitro models for local drug delivery within tissue-like structures are lacking. Fibroblast-populated collagen lattices have long been used as a surrogate model for tissue contraction to screen potential anti-scarring treatments [ 32 ], especially in the context of preventing post-surgical scarring after glaucoma filtration surgery [ 12 , 33 , 34 ], using bulbar conjunctiva and/or Tenon’s capsule fibroblasts [ 1 , 35 , 36 ]. However, these have been of limited use to the development of less toxic anti-scarring drugs and/or new delivery systems, as the soft, loose gels do not suitably mimic human tissue composition and stiffness, and are not readily amenable to incorporation of slow release drug delivery devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraoperative drug delivery is one of the key ways of preventing and treating ocular fibrosis, yet in vitro models for local drug delivery within tissue-like structures are lacking. Fibroblast-populated collagen lattices have long been used as a surrogate model for tissue contraction to screen potential anti-scarring treatments [ 32 ], especially in the context of preventing post-surgical scarring after glaucoma filtration surgery [ 12 , 33 , 34 ], using bulbar conjunctiva and/or Tenon’s capsule fibroblasts [ 1 , 35 , 36 ]. However, these have been of limited use to the development of less toxic anti-scarring drugs and/or new delivery systems, as the soft, loose gels do not suitably mimic human tissue composition and stiffness, and are not readily amenable to incorporation of slow release drug delivery devices.…”
Section: Resultsmentioning
confidence: 99%
“…Our own work using ex-vivo porcine conjunctival fragments has shown that these mimic more faithfully aspects of conjunctival scarring than simple 3D fibroblast-loaded collagen matrices, including physiologically relevant contraction kinetics [ 9 ]. Further work using porcine 3D cultures of mixed Tenon’s capsules and bulbar conjunctival fibroblasts has shown these to be sensitive to known triggers of fibrosis (inflammatory growth factors, shear stress and aqueous humour exposure), confirming that porcine cells cultured in vitro can be used to model some aspects of the conjunctiva response to fibrosis [ 36 ]. However, these studies used mixed cells in moderately stiff collagen gels, which did not accurately recapitulate the Tenons’ capsule/bulbar conjunctiva organisation, in which the Tenons’ capsule tissue sits between the stiff sclera and the conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lines as well as primary cells of animal and human origin are used in ophthalmology while organoid models of the eye are still in their infancy (21). Cell systems may include primary human cells of one type or co-cultures in which different cell types of one tissue are cultivated together to account for intracellular, e.g., cytokine-mediated communication (22,23).…”
Section: Cell Systemsmentioning
confidence: 99%
“…Cell lines as well as primary cells of animal and human origin are used in ophthalmology while organoid models of the eye are still in their infancy (20). Cell systems may include primary human cells of one type or co-cultures in which different cell types of one tissue are cultivated together to account for intracellular, e.g., cytokine-mediated communication (21,22).…”
Section: Cell Systemsmentioning
confidence: 99%